The Effect of Slope Slope on the Distribution of Nickel Laterite at PT Sentratama Karya Cemerlang, South Konawe Regency, Southeast Sulawesi Province - Bakri, Suriyanto; Hardianto; Bakri, Hasbi; Fadli Heriansyah, Andi (Journal of Geology and Exploration, 2023)
The Morphology That Develops In The Study Area Consists Of Undulating Hills. Based On The Results Of The Slope Analysis, The Research Area Is Divided Into Several Slope Classes, Namely Flat Slopes, Gentle Slopes, Sloping Slopes And Steep Slopes. The Process Of Forming Laterite Nickel Deposits Will Be Greatly Influenced By The Slope Conditions. In The Research Area, Slopes That Have A High Percent Slope, The Thickness Of The Deposits That Will Be Formed Will Be Thinner, Ranging From 6-12 Meters, On The Other Hand, Slopes That Have A Low Percent Slope, The Thickness Of The Deposits That Will Be Formed Will Be Thicker, Ranging From 18-30 Meters. Therefore, This Study Aims To Determine The Effect Of Slope On The Distribution Of Nickel Laterite, Namely To Determine The Slope Of The Slope On Nickel Laterite At Pt Sentratama Karya Cemerlang, Laeya District, South Konawe Regency, Southeast Sulawesi Province